The Influence of the Integrated Approach on Students Reading Ability in Lessons Indonesian Serang City - Gunardi, Ari; Nursehah, Uvia; Nahriyah (LPPM Universitas Primagraha, 2022)
The purpose of this study was to determine the effect on students' reading comprehension skills with an integrative approach to Indonesian class IV subjects at SDN Cilaku, Serang City, Banten. The research was carried out in class IV of SDN Cilaku, Serang City, for the academic year 2021/2022, totaling 81 students. The design of this study was quasi-experimental. The data collection techniques used were observation and documentation. The analysis techniques used is descriptive statistics and differential statistics. Based on the research that has been done and the processing of research results in the form of pretest and posttest in both experimental classes, the results obtained are sig (2 tailed) < 0.05 where the experimental class A and B have a value of 0.00 < 0.05 using 2 directions, one independent sample. test, then H0 is rejected and H1 is accepted. This means that there is an influence on students' reading comprehension skills with an integrative approach to Indonesian class IV subjects at SDN Cilaku, Serang City, Banten.